2016
DOI: 10.1016/j.devcel.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Cell Invasion Requires Cooperative Regulation of Persistent Microtubule Growth by SLAIN2 and CLASP1

Abstract: Summary Microtubules regulate signaling, trafficking and cell mechanics but the respective contribution of these functions to cell morphogenesis and migration in 3D matrices is unclear. Here, we report that the microtubule plus-end tracking protein (+TIP) SLAIN2, which suppresses catastrophes, is not required for 2D cell migration but is essential for mesenchymal cell invasion in 3D culture and in a mouse cancer model. We show that SLAIN2 inactivation does not affect Rho GTPase activity, trafficking and focal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 70 publications
6
65
0
Order By: Relevance
“…SLAIN2 is known to link microtubule plus end‐tracking proteins, binding to cytoplasmic linker proteins (CLIPs) and CLIP‐associated proteins, and controlling microtubule growth . Furthermore, it was demonstrated that invasive growth requires regulated microtubule growth by SLAIN and interaction partners . Future studies should ascertain how atRA signaling regulates SLAIN2 protein expression in platelets, and the function of this protein in health and disease.…”
Section: Discussionmentioning
confidence: 99%
“…SLAIN2 is known to link microtubule plus end‐tracking proteins, binding to cytoplasmic linker proteins (CLIPs) and CLIP‐associated proteins, and controlling microtubule growth . Furthermore, it was demonstrated that invasive growth requires regulated microtubule growth by SLAIN and interaction partners . Future studies should ascertain how atRA signaling regulates SLAIN2 protein expression in platelets, and the function of this protein in health and disease.…”
Section: Discussionmentioning
confidence: 99%
“…To establish a causal connection between MT overgrowth and defects in immune synapse formation, we sought for a way to mildly inhibit MT growth in KIF21B-KO cells. Our previous work has shown that a low dose of vinblastine mildly perturbs growth and promotes catastrophes but does not induce MT depolymerization (Bouchet et al, 2016;Mohan et al, 2013). Indeed, at a low (0.5 nM) vinblastine concentration, MT network was preserved and was similar to that in control cells but different from KIF21B-KO cells, as no circular MT bundles were present at the cell periphery (compare Figure S4B to Figure 2A).…”
Section: Mt Growth Inhibition With Vinblastine Rescues the Defects Inmentioning
confidence: 99%
“…The last decade led to a sharp rise in evidence for microtubules as central structural components that counter compression, [ 30,46,62,64–69,77,105 ] thus contributing to the mechanical state of epithelial tissues. [ 77,78 ] Yet, to date our understanding of microtubule mechanics is strongly influenced by insights gained from in vitro models that do not reveal the complexity of mechanisms controlling the interplay between microtubules and their effectors (e.g., motor proteins, MAPs, modification enzymes).…”
Section: Discussionmentioning
confidence: 99%
“…Despite their favorable biophysical properties and their widespread deployment in a large variety of cellular contexts, our understanding of the mechanical contribution of microtubules to tissue formation is only now emerging. In the past years, several studies demonstrated their mechanical contribution to cell mechanics [ 46,62–69 ] and a tensegrity model was proposed, suggesting that the ability of microtubules to withstand compression balance tensional forces in vivo (reviewed in ref. [70]).…”
Section: Microtubules In Cell Mechanicsmentioning
confidence: 99%